Assessing Patient Goals for Gender-Affirming Hormone Therapy: A Standardized Patient Case for Medical Students - Sabina T. Spigner; Nicole V. Rivera; Eloho Ufomata; Elyse G. Mark; Victoria Grieve; Morgan Faeder; Valerie L. Fulmer; Reed Van Deusen; Catherine Gowl; Dena Hofkosh; Kristen L. Eckstrand (Association of American Medical Colleges, 2023)
Introduction Inadequate coverage of transgender and gender-diverse (TGD) health in the UME curriculum contributes to the scarcity of competent physicians to care for TGD patients. Increasing TGD health skills-based curricula in UME can help address TGD health disparities. We developed a standardized patient (SP) case to assess TGD health skills-based competencies and attitudes among medical students. Methods An interdisciplinary team, including individuals with lived TGD experience, developed the SP case that was completed by second-year medical students at the University of Pittsburgh School of Medicine in January 2020. After the TGD SP session, students and faculty completed a postsession survey to assess the degree to which the case met the learning objectives. Students were assessed via self-reports, faculty reports, and SP video evaluations. Results Seventy second-year medical students, 30 faculty facilitators, and eight SPs participated in 2020. Students reported being significantly more prepared to care for TGD patients (Z = −5.68, p < .001) and to obtain a gender history (Z = −5.82, p < .001). Both faculty and students felt that skills for caring for TGD patients were important in medical education and agreed the case should remain in the curriculum. Discussion The case effectively honed and assessed students' ability to collect a gender history and discuss goals for hormone therapy with TGD patients. It should complement ongoing curricula to effectively train medical students in TGD health care. Developing these skills in students directly addresses the barriers that many TGD patients experience in health care settings.